A Critical Discourse Analysis of Hate Speech directed towards Iraqi TV Series’ Performers On Social Media - Mahmood Almuslehi (الأستاذ, 2023)
This study investigates  online hate speech directed against  Iraqi actors and actresses in the online environment of Facebook and Instagram platforms.  Fairclough’s  (2001) Three-Dimensional Model is employed  in this study to  unravel the delicate fabric of language used in hate remarks, demonstrating its function in generating discriminatory discourse and falling under the broad purview of Critical Discourse Analysis (CDA). To provide nuanced insights into the mechanisms by which online hate speech operates and the wider socio-cultural implications it engenders, it also seeks to uncover the latent ideologies and belief systems that underlie hate comments and to illuminate their intersections with dominant ideologies.